Grand-parenting experiences among adults with a history of depression: a mixed-methods study - Izquierdo, Adriana (Gen Hosp Psychiatry, 2014)
OBJECTIVE: Grand-parenting is an important social role but how adults with a history of depression experience grand-parenting is unknown; we describe grand-parenting experiences reported by an ethnically-diverse sample of adults with a history of depression. METHOD: Mixed-methods study using semi-structured interviews of adults at 10-year follow-up and quantitative data collected over 9 years from 280 systematically-sampled participants from a longitudinal, multi-site trial of quality-improvement interventions for depressed primary care patients; of 280, 110 reported noncustodial grand-parenting experiences. RESULTS: Of 110 adults reporting grand-parenting experiences, 90 (82%) reported any positive experience such as special joy; 57 (52%) reported any stressful experience such as separation; 27 (34%) reported mixed experiences. Adults with chronic or recent depression were significantly more likely than their respective counterparts to report any stressful experience (p<0.05). There was no significant association between depression status and reporting a positive experience. CONCLUSION(S): Grand-parenting was a highly salient and positive experience as reported by ethnically-diverse adults 10 years after being identified as depressed in primary care. Depression status was associated with reporting stressful but not positive experiences. Specific themes underlying positive and stressful experiences may have implications for developing strategies to enhance quality of life for adults with a history of depression who are grandparents.